A comparative study of mental skills level between athletes according to the variable of experience, specialization - حمزة بن ساحلي; عبدلي فاتح (Journal of Sport Science Technology and Physical Activities, 2021)
The Object of the study aims to identify the differences in mental skills among athletes according to the variable of experience, sports specialization for this purpose, we used the comparative-descriptive method On a sample composed of 40 (10 football) (10 handball) (10 karate) (10 judo) at range of 15-30 years athlete Chosen as random sample, and for data collection, we used a psychological skills scale After collecting the results and having treated them statistically, we conclude there was significant differences in each of experience and specialty variable On this basis, the study recommended Taking into account these differences when dealing with athletes on the psychological level